Comparative Advantage and Long-Run Growth - Grossman, Gene M.; Helpman, Elhanan (American Economic Review, 1990)
We construct a dynamic, two-country model of trade and growth in which endogenous technological progress results from the profit-maximizing behavior of entrepreneurs. We study the role that the external trading environment and that trade and industrial policies play in the determination of long-run growth rates. Cross-country differences in efficiency at R&D versus manufacturing (i.e., comparative advantage) bear importantly on the growth effects of economic structure and commercial policies.